Primary Health Care - nursing system to prevent and/or minimize health problems - Raimunda Magalhães da Silva; Fátima Luna Pinheiro Landim (Universidade Federal do Ceará, 2012)
The concept of social protection is an issue of discussion, once it is present in every field of knowledge, concurrently with the implementation and improvement of the Unified Health System (SUS). Resulting from this greater perception of inequalities and promoting the creation of services seeking the universal access. In this direction, the Primary Health Care (PHC) advanced substantively over the past years. Ordinance No. 648 GM/2006 approved this National Policy, establishing the review of guidelines and standards for its organization, which uses as structural axis the Family Health Strategy.